PLANT PATHOLOGY - GEORGE N. AGRIOS; GEORGE N. AGRIOS (AMSTERDAM Academic Press, 2006)
This book covers the history of plant pathology, the basic consepts of plant disease, effects of environmental factors on disease initiation and development, and the latest information on epidemiology and control of plant diseses.
Plant disease Environmental factors Parasitism
Keywords: Plant disease; Environmental factors; Parasitism